Impact of Core-self Evaluation and Job Satisfaction on Turnover Intentions: a Study of Indian Retail Sector - Chhabra, Bindu (Organizations and Markets in Emerging Economies, 2018)
Attrition is the major problem in the Indian Retail Industry which experienced the attrition rate of 19.4% in FY 2016 according to KPMG Annual Compensation Trends Survey 2017-18. The focus of these organizations is to reduce turnover by focusing on the underlying factors leading to turnover intentions and actual turnover. The present study was conducted to explore the effect of job satisfaction and core self-evaluation on turnover intentions. The purpose of the study was also to see if core self-evaluation (CSE) moderates the relationship between job satisfaction and turnover intentions. The study was conducted using structured questionnaires for measuring the above-mentioned variables. The sample of the study was 347 salespersons from various retail organizations working in Delhi and NCR. Hierarchical multiple regression showed that both job satisfaction and CSE were negatively related to turnover intentions. Also, CSE was found to moderate the relationship between job satisfaction and turnover intentions such that the relationship was stronger for the employees with low core self-evaluation. The present study has important implications for policy makers in the retail sector. Managers should use strategies to increase job satisfaction in order to curb high attrition in this sector. They must be aware of the moderating role played by personality attributes in the relationship between job satisfaction and turnover intentions.
Keywords: Indian retail sector; salesperson; core self-evaluation; job satisfaction; turnover intentions